Biomechanical Evaluation of Different Plate Configurations for Midshaft Clavicle Fracture Fixation: Single Plating Compared with Dual Mini-Fragment Plating. Issue 1 (January 2022) - Kitzen, Joep; Paulson, Kent; Korley, Robert; Duffy, Paul; Martin, C. Ryan; Schneider, Prism S.
Abstract : Background: Dual-plate constructs have become an increasingly common fixation technique for midshaft clavicle fractures and typically involve the use of mini-fragment plates. The goal of this technique is to reduce plate prominence and implant irritation. However, limited biomechanical data exist for these lower-profile constructs. The study aim was to compare dual mini-fragment orthogonal plating with small-fragment clavicle plates for biomechanical noninferiority and to determine if an optimal plate configuration could be identified using a cadaveric model. Methods: Twenty-four cadaveric clavicles were randomized to 1 of 6 groups, stratified by computed tomography-based bone mineral content (BMC): precontoured superior or anterior fixation using a single 3.5-mm Locking Compression Plate (LCP), and 4 different dual-plating constructs utilizing 2.4-mm and 2.7-mm Adaptation plates or LCPs. An inferior butterfly fracture was created. Axial, torsional, and bending (anterior and superior surface loading) stiffnesses were determined through nondestructive cyclic testing, followed by a load-to-failure test in 3-point superior surface bending. Results: For axial stiffness, the 2 dual-plate constructs with a superior 2.4-mm and anterior 2.7-mm plate (either Adaptation or LCP) were significantly stiffer than the other 4 constructs (p = 0.021 and p = 0.034). For both superior and anterior bending, the superior 2.4-mm and anterior 2.7-mm plate constructs were significantly stiffer when compared with the 3.5-mm superior plate (p = 0.043). No significant differences were found in torsional stiffness or load to failure between the different constructs. Conclusions: Dual plating using mini-fragment plates is biomechanically superior for the fixation of midshaft clavicle fractures when compared with a single, superior, 3.5-mm plate and has biomechanical properties similar to those of a 3.5-mm plate placed anteriorly. With the exception of axial stiffness, no significant differences were found when different dual-plating constructs were compared with each other. Clinical Relevance: This study validates the use of dual plating for midshaft clavicle fractures.